Low levels of circulating alpha-1 antitrypsin are associated with spontaneous abortions*. (December 2013) - Madar, Tamar; Shahaf , Galit; Sheiner, Eyal; Brazg, Jared; Levinson, Justin; Yaniv Salem, Shimrit; Twina, Guy; Baron, Joel; Mazor, Moshe; Holcberg, Gershon; Lewis, Eli C
Abstract Objective: Alpha-1 antitrypsin (AAT), a circulating anti-inflammatory molecule, rises four- to sixfold during acute phase responses and during pregnancy. AAT deficiency is linked with various pregnancy complications. The aim of this study is to determine plasma concentrations and activity of AAT and serum cytokine levels in blood samples from women undergoing spontaneous abortions as compared with elective abortions. Methods: A prospective case–control study consisted of patients with sporadic abortions (n = 15), recurrent spontaneous abortions (n = 14) and healthy pregnancies going through elective terminations (n = 11). Circulating AAT and cytokine levels were determined before dilatation and curettage. Results: AAT levels were lower in both recurrent and sporadic spontaneous abortion groups compared with healthy pregnancies (1.421 ± 0.08, 1.569 ± 0.14 and 3.224 ± 0.45 mg/ml, respectively, p < 0.001). Reduced AAT levels correlated with elevated proinflammatory cytokines. Conclusions: AAT levels in patients with either sporadic or recurrent spontaneous abortions were lower than normal pregnancies, and were associated with an inflammatory profile. Future studies should examine larger cohort groups, effects of earlier time-points and the influence of antithrombotic therapy in such patients who are diagnosed with relatively low levels of circulating AAT, in an effort to improve pregnancy outcomes.